Estudo sobre Campylobacter jejuni e Campylobacter coli em crianças da área urbana de Fortaleza, Ceará/Brasil : Identificação genética, inflamação intestinal e impacto no estado nutricional - Quetz, Josiane da Silva (2009)
Campylobacter jejuni and Campylobacter coli are important etiologic agents of worldwide diarrheal disease. Campylobacter sp. infection is usually identified by a 72 hour microbiological culture that identifies the genus of the responsible organism. Our main goal was to investigate the prevalence of C. jejuni and C. coli in children, aged 2-36 months, from urban Fortaleza, CE, Brazil, in an observational epidemiological case-control study using, as a tool of detection, the polymerase chain reaction (PCR). Our other goals were to investigate the nutritional impact of infection (cases) or colonization (controls) for Campylobacter sp., to determine the presence of three virulence genes of C. jejuni cytolethal distending toxin (CDT), and to evaluate the occurrence of inflammation in intestinal infections caused by Campylobacter sp. The study population consisted of 83 cases and 83 controls, where the cases consisted of children with a history of diarrhea in the 14 days prior to selection for the study. We assessed socioeconomic parameters through an epidemiological questionnaire. Anthropometric measurements were collected to determine z-score parameters for assessing the nutritional status of the children. Detection of Campylobacter from frozen samples was performed by enzyme-linked immunosorbent assay (ELISA) and PCR. Also, using PCR technology, we investigated the presence of C. jejuni genes cdtA, cdtB and cdtC. Intestinal inflammation was assessed by semi-quantitative ELISA detection of fecal lactoferrin (LFF). PCR technology detected C. jejuni in 9.6% of the cases (8/83) and 7.2% of the controls (6/83), while C. coli was detected in 6.0% of the cases (5/83) and 1.2% of the controls (1/83). CDT genes were found in 50% of hipO+ samples (7/14). There was a significant difference (p <0.05) in the weight for age z-scores (WAZ) and the weight for height z-scores (WHZ) between case and control carriers of C. jejuni, where case carriers showed lower average WAZ and WHZ than control carriers. Moreover, in the case group, carriers of C. jejuni showed a lower WHZ average than that of non-carrier cases of C. jejuni. More than 80.0% of the children studied had intestinal inflammation characterized by high levels of LFF regardless of the presence of diarrhea and Campylobacter sp. In conclusion, our findings corroborate data in the scientific literature related to the prevalence of C. jejuni and C. coli in pediatric populations, the existence of asymptomatic carriers and an association between the detection of the microorganism and malnutrition. In addition, our data suggest a genetic variability among the strains of C. jejuni detected in the study population, related to presence o absence of CDT genes.